The role of cyclic nucleotides in the model plant arabidopsis - Malinna Jusoh (University of Oxford, 2011)
Adenylyl cyclases (ACs) catalyze the formation of adenosine3',5'-cyclic monophosphate (cAMP) from adenosine 5'-triphosphate (ATP). The Arabidopsis genome contains two genes, At3g14460 (AC1) and At3g14470 (AC2) which have an aminoterminal nucleotide binding domain and sequence homology to maize AC. Expression of AC1 and AC2 complemented the E.coli cAMP mutant, cya suggesting that both proteins produce functional cAMP in vivo. Gene expression studies using RT-PCR and promoter- GUS staining showed that AC1 is expressed in root tips, inflorescence and anthers, while AC2 is expressed in stem, roots, cauline leaves, senescent leaves, and inflorescences. TDNA insertion mutants of ac1 and ac2 showed a delay and a reduction in germination under salt stress. Conversely, overexpression of AC1 and AC2 conferred some protection against salt stress. Taken together, I infer that cAMP may have a role in salinity tolerance.